MEDIASI KOMPETENSI PEGAWAI DALAM HUBUNGAN ANTARA KNOWLEDGE SHARING DENGAN PENINGKATAN KINERJA PEGAWAI BANK UMUM SYARIAH - Dematria Pringgabayu; Wawan Hermawan (Jurnal Manajemen dan Bisnis (JMB), 2020)
AbstractThis study was conducted to determine if knowledge sharing and competence, has a positive and significant influence on employee performance in the Syariah Bank Company in Indonesia. This study has three variables, namely knowledge sharing and competence as an independent variable and the performance of employees as the dependent variable. Data were obtained through interviews and questionnaires to employees in Syariah Bank Companies in Indonesia with a sample size of 145 people. This research method using descriptive method and the method of verification. Data processing is done by using path analysis. The results of this study indicate that Knowledge sharing positive effect of 28.9% in the form of employee performance, which means that with improvements in the implementation of knowledge sharing Syariah Bank Company, then it will be better the performance owned employee. Besides competence also have considerable influence, namely 10.2% in the form of employee performance  Keywords : Knowledge sharing, competency, employee performance